Analisis Perbandingan Risiko Keuangan Bank Konvensional Dan Bank Syariah (Studi Pada Bank Mandiri Konvensional Dengan Bank Syari’ah Mandiri) - Rahimah, Evida; Nasution, Budiman Rosyadi; Abdullah, Ujang; Subaktiar, Subaktiar; Insy Sinaga, Riny Viri (Universitas Labuhanbatu, 2023)
The purpose of this study is the comparison of financial risk in conventional banks and Islamic banks. The object of this study was Bank Mandiri and Bank Syariah Mandiri with an observation period of 2 years from 2018 to 2019. The type of research taken in this study is descriptive comparative qualitative. The method of analysis used is Z-score discriminant analysis by comparing the level of financial risk between Bank Mandiri and Bank Syariah Mandiri. The results indicate the level of financial risk of Bank Mandiri is better than Bank Mandiri.